2013
DOI: 10.1111/resp.12181
|View full text |Cite
|
Sign up to set email alerts
|

Quadriceps strength and endurance in fibrotic idiopathic interstitial pneumonia

Abstract: Quadriceps strength and endurance are reduced in patients with fibrotic IIP compared with healthy controls, but are less tightly correlated with exercise performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 37 publications
3
44
0
2
Order By: Relevance
“…In a study by NISHIYAMA et al [50], the quadriceps muscle force of 41 IPF patients studied retrospectively was reduced on average to 65% predicted and represented an independent predictor of V′O 2 peak at the end of exercise. A more recent prospective study showed reduced quadriceps strength and endurance in IPF and nonspecific interstitial pneumonia patients, compared to age-matched controls [51]. A similar relationship between quadriceps peak torque and both peak workload and functional exercise capacity has been documented in patients with sarcoidosis [52].…”
Section: Peripheral Muscle Dysfunctionmentioning
confidence: 73%
“…In a study by NISHIYAMA et al [50], the quadriceps muscle force of 41 IPF patients studied retrospectively was reduced on average to 65% predicted and represented an independent predictor of V′O 2 peak at the end of exercise. A more recent prospective study showed reduced quadriceps strength and endurance in IPF and nonspecific interstitial pneumonia patients, compared to age-matched controls [51]. A similar relationship between quadriceps peak torque and both peak workload and functional exercise capacity has been documented in patients with sarcoidosis [52].…”
Section: Peripheral Muscle Dysfunctionmentioning
confidence: 73%
“…Reduced quadricep strength and endurance was seen in patients with fibrotic idiopathic interstitial pneumonias relative to healthy controls [Mendoza et al 2014]. However, there was no association between 6MWD and quadricep force [Mendoza et al 2014].…”
Section: Muscle Dysfunctionmentioning
confidence: 99%
“…There are similarities and differences in peripheral muscle dysfunction between ILD and COPD. Studies in both populations report reduced voluntary strength of the quadriceps as the most common finding of peripheral muscle function; preferential muscle weakness in the lower versus upper extremities; and have a smaller body of evidence of reduced non-volitional quadriceps strength and endurance [3,18,35,37].…”
Section: Discussionmentioning
confidence: 99%
“…One study did not find reductions in volitional quadriceps muscle strength compared to healthy controls, however did report reduced non-volitional quadriceps muscle strength and endurance. [37] Quadriceps force or torque was reduced to a greater extent than handgrip force, which was reported to be normal in some studies, or marginally reduced (range: 84-97% predicted). Muscle strength and lower extremity function was also measured using short functional tests targeting muscle strength (3 studies); and lower performance in individuals with ILD compared to healthy controls or predicted values was reported.…”
Section: Findings Of Muscle Strength and Endurancementioning
confidence: 99%
See 1 more Smart Citation